Study of etiopathogenesis and management of epistaxis in tertiary care centre - M., Muniraju; P. R., Julie (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Background: Epistaxis is one of the most commonly addressed complaints in patients visiting outpatient department of ENT. This study aimed to determine common etiologies and management of epistaxis in a Tertiary care centre. Methods: This prospective descriptive study was conducted with 60 patients selected by consecutive sampling presented to our hospital with epistaxis between the years 2021-2022. Results: Incidence of epistaxis was more in males (58.33%) with male to female ratio of 1.4:1. Most common age group was between 10-49 years (68.33%). The commonest etiology was idiopathic (30%). When the cause was present, trauma was the most common reason mainly in young adults (13.33%) followed by hypertension (11.67%). The most common site of epistaxis was noted in the anterior nasal cavity (45%) where Little’s area (20%) was the most common location. Most cases were managed by conservative non-surgical treatments alone (55%) like anterior and, or posterior nasal packing, chemical/ electro-cauterization, foreign body removal, and blood components transfusion. Almost an equal number of patients underwent Surgical management in our hospital (45%) as it is a tertiary care centre. Conclusions: Epistaxis is an ENT emergency seen in all age groups, more common in adolescents and young adults, males are affected more than females. The cause of epistaxis was not known in most cases, i.e., Idiopathic. Most of the cases can be managed by non-surgical treatment. It is necessary for the treating doctor to accurately diagnose the etiology of the case, and bleeding site and treat accordingly.